Innovation and Technology: A Panacea to Teaching and Learning Challenges during the Covid-19 Lockdown in South Africa - Kemi O. Adu; Kazeem Ajasa Badaru; Ntombozuko Duku; Emmanuel O. Adu (Research in Social Sciences and Technology, 2022)
Innovation and technology brought by the 4th Industrial Revolution (4IR) have become an urgent reality to all teachers because of the need for a virtual classroom. In South Africa, over 13 million students in almost 25,000 schools have been affected by the COVID-19 lockdown. Most school teachers were not trained for online teaching, which was the only safe method of teaching during the lockdown period. This study, therefore, investigated how innovation and technology were utilised to mitigate the virtual classroom problems during the COVID-19 lockdown. This study employed a qualitative research approach using interviews to collect data based on the phenomenological research design. The sample for this study consisted of 12 lecturers purposively drawn from one university in the Eastern Cape Province of South Africa. Thematic content analysis was performed on the data. The findings revealed that a majority of the participants have poor pedagogical skills especially those related to using technologies such as Blackboard, Microsoft Teams, and V-Drive on computers for online teaching engagements during the COVID-19 lockdown; strategies utilised by the participants for their teaching activities during the lockdown included Microsoft Teams, WhatsApp voice notes, email attachments for sending bulky teaching materials to students, and other Computer-instructional resources. Thus, this study recommends an urgent need for capacity development workshops to equip lecturers with computer and ICT skills, knowledge, and strategies for online teaching delivery and increased provision of adequate learning and teaching facilities in all public educational institutions, including those in the rural areas.